Agricultural technology and food policy to combat iron deficiency in developing countries - Bouis, Howarth E. (International Food Policy Research Institute, 1994)
Breeding for food-staple plant varieties that load high amounts of iron and zinc in their seeds holds great promise for making a significant, low-cost, and sustainable contribution to reducing iron and zinc deficiencies in humans in developing countries. This strategy also may well have important spinoff effects for increasing farm productivity in developing countries in an environmentally-beneficial way. Understanding how household incomes, food prices, and culturally-based preference patterns interact to drive food consumption and nutrient intake patterns can provide crucial background information for designing effective nutrition intervention programs. This paper presents findings from a project titled Food Policy and Agricultural Technology to Improve Diet Quality and Nutrition, organized by the International Food Policy Research Institute (IFPRI), implemented by the Consultative Group on International Agricultural Research (CGIAR) and other collaborating organizations, and funded by the Office of Health and Nutrition of the United States Agency for International Development (USAID). One strategy is to enhance the micronutrient content of edible portions of crops through plant breeding. Plant breeding, which in this context may be viewed as a form of fortification, has tremendous potential for improving micronutrient intakes. This strategy is discussed in the paper, which summarizes one aspect of the discussion and papers presented at an initial organizational workshop for the project held in Annapolis, Maryland, U.S.A., January 10-12, 1994.